Can point‐of‐care testing improve access to diagnostic screening and testing for people with learning disabilities? Exploring perspectives to improve access and equity. (13th December 2019) - Giles, Karen; Ling, Jonathan; Gordon, Isabel
Accessible summary: People with learning disabilities, like everyone else, need to have their health checked, but this can sometimes be difficult. We asked people with learning disabilities and the people who look after them what they thought about how they have blood tests done or their hearing checked. We found out the things that make it a positive experience. We learnt that people with learning disabilities and the people who look after them thought point‐of‐care testing would be a good idea. We learnt what things they thought should be put in place to make this type of testing work well for them. Abstract: Background: People with learning disabilities have an increased risk of diabetes, cardiovascular disease and hearing loss. This study explored service users' and health professionals' perspectives and experiences of adopting minimally invasive diagnostic and screening devices, known as point‐of‐care testing (POCT) as a means of improving access and engagement. Materials and Methods: Focus groups and semi‐structured interviews were undertaken with attendees at a nonhealthcare day centre, specialist learning disability clinical network and national leads as well as researchers into learning disability and point‐of‐care issues. Thematic analysis of the data was undertaken. Results: There was a lack of awareness and experience of POCT across the users and health professionals. Despite this, on seeing the devices and discussing application there was strong support and acceptability across all participants for their use so long as individual needs were addressed. There was no consistent sense of where this testing should be done but support for the flexibility this could provide in terms of nonmedicalised locations and individual needs. Strategies for success included the use of specific adjustments such as the presence of a known carer, pre‐testing information in an appropriate format and taking into account each individual's preferences. Conclusions: POCT is considered a viable and useful method for improving access to testing for people with learning disabilities. Adoption barriers in implementation identified as specific to the field of learning disabilities included lack of POCT awareness and diagnostic overshadowing concerns, and adjusting for individualised needs is essential.